ANALYSIS OF FACTORS CAUSING LOW STUDENT READING INTEREST IN THE DIGITAL ERA AND STRATEGIES TO OVERCOME IT - Dr. Suryaningsih, S.S.,M.Pd.K (International Journal of Teaching and Learning, 2025)
Interest in reading is a fundamental aspect in students' intellectual and academic development. However, in the digital era, students' interest in reading tends to decline due to various factors, such as increasing distraction from technology, changes in information consumption patterns, and lack of support from the family and school environment. This research aims to analyze the factors that cause students' low interest in reading in the digital era and identify strategies that can be implemented to improve reading habits. The research method used is a literature review by analyzing various academic sources, such as scientific journals, books, and research reports that discuss interest in reading, the impact of digitalization on literacy, as well as innovative approaches to literacy learning. The research results show that the main causes of students' low interest in reading include increased dependence on instant digital content, a lack of literacy culture in the family environment, limited innovation in learning methods at school, and a lack of interesting and varied reading materials. To overcome this problem, several strategies that can be implemented include building a culture of literacy at home, limiting excessive digital distractions, integrating technology in literacy learning, and utilizing gamification and digital reading applications to increase the appeal of reading. By implementing the right strategies and collaboration between families, schools, and wise use of technology, students' interest in reading in the digital era can be increased significantly.